Rancang Bangun Sistem Pendeteksian Objek Halang Dan Pengereman Otomatis Pada Robot Forklift - Lutfi Wahyu Aryanto; Sujono Sujono; Akhmad Musafa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Forklifts are tools to move large and large items to the place you want to go, forklifts are widely used in the warehousing section in running forklifts an operator is needed. The problems that occur include forklifts crashing into goods in the warehouse, forklifts crashing into forklifts because of the problems that occur, a prototype of an obstacle object detection system and automatic braking on a forklift robot is made. The parts of the forklift robot are the obstacle detection system in the form of (ultrasonic sensor and pixy camera) and the automatic braking system, namely (motor driver and dc motor). ). The working principle of the forklift robot is that the forklift follows the line that has been made if the detection system can detect an obstacle object, the braking system will automatically brake with a robot distance of 20 cm from the obstacle object, after that the buzzer will turn on and provide notification if an obstacle object is detected, if the obstacle object is moved, the robot will move again until the finish. In the overall robot testing scheme, the robot will be given several objects in the form of blue block-shaped objects, red block-shaped objects and green triangular objects, the forklift robot testing scheme is carried out 6 times with objects placed in different positions. The result of testing the forklift robot is that the robot can detect obstacle objects in the form of red and blue blocks and green triangles if the position of the object is in front of the forklift robot The conclusion is that the forklift robot can detect obstacles if the object is in front of the forklift robot.